2023
DOI: 10.3390/ani13132159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inclusion of Dietary Bitter Gourd (Momordica charantia) on the Performance and Carcass Characteristics of Pigs: Potential Application in the Feed Chain

Abstract: The objective of this study was to determine the effect of bitter gourd (BG) leftovers (stems and leaves) as an alternative dietary ingredient on pig performance, carcass characteristics, serum parameters (urea, insulin, and leptin levels), and faecal consistency. Healthy Tempo × Great Yorkshire and Landrace pigs (N = 240; 120 gilts and 120 boars) weighing 25.8 kg (9–10 weeks of age) were randomly assigned to three treatments (eight pens per treatment; each pen with five gilts and five boars). The three treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An elevation in plasma insulin concentrations may promote whole body protein anabolism in young growing animals, thereby increasing production and reducing nitrogen excretion [ 42 ]. A recent study by us [ 43 ] showed that 0.65–1.3% inclusion of Bitter gourd stems and leaves in feed of growing pigs had no effects on plasma insulin and urea concentrations and on pig performance. These inclusion levels of Bitter gourd stems and leaves in feed were however 3-fold to 6-fold lower compared to the present study (4% inclusion level).…”
Section: Discussionmentioning
confidence: 99%
“…An elevation in plasma insulin concentrations may promote whole body protein anabolism in young growing animals, thereby increasing production and reducing nitrogen excretion [ 42 ]. A recent study by us [ 43 ] showed that 0.65–1.3% inclusion of Bitter gourd stems and leaves in feed of growing pigs had no effects on plasma insulin and urea concentrations and on pig performance. These inclusion levels of Bitter gourd stems and leaves in feed were however 3-fold to 6-fold lower compared to the present study (4% inclusion level).…”
Section: Discussionmentioning
confidence: 99%
“…In case of mortality, the cause of death was recorded. Faecal consistency (see for protocol Guan et al [18]) was determined daily at the pen level between day 0 and 11 post-weaning and at the individual level between day 11 and 19 post-weaning.…”
Section: Animals and Animal Housingmentioning
confidence: 99%